2020
DOI: 10.1111/tid.13486
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for intra‐abdominal fungal infection after simultaneous pancreas‐kidney transplantation: A single‐center retrospective experience

Abstract: Background Data on the risk factors and outcome of intra‐abdominal fungal infections (IAFI) following simultaneous pancreas‐kidney transplantation (PKT) are scarce. Materials/methods A retrospective monocentric study was conducted on all patients who underwent simultaneous PKT from January 2007 to December 2016. Deep sites positive cultures for fungi during the first post‐transplantation year were collected. Clinical, radiological, and microbiological data of proven and probable invasive fungal infections were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…3 On the contrary, 47% of PTRs developed IFI despite the administration of prophylaxis with fluconazole for 7 days in a recently published French series that only included 16 patients. 6 This large disparity in incidence rates might be justified, among other reasons, by the disparate criteria applied to define infection across available studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3 On the contrary, 47% of PTRs developed IFI despite the administration of prophylaxis with fluconazole for 7 days in a recently published French series that only included 16 patients. 6 This large disparity in incidence rates might be justified, among other reasons, by the disparate criteria applied to define infection across available studies.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of IFI was estimated at 8% in an Austrian study that included 72 PTRs with enteric exocrine pancreas drainage and fluconazole prophylaxis between 2002 and 2004 3 . On the contrary, 47% of PTRs developed IFI despite the administration of prophylaxis with fluconazole for 7 days in a recently published French series that only included 16 patients 6 . This large disparity in incidence rates might be justified, among other reasons, by the disparate criteria applied to define infection across available studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors also reported that fungal infections were independent risk factors for severe pancreatic graft dysfunction [ 71 ]. A French cohort analyzing 15 patients of KPT over 11 years reported IFI in seven (47%) cases, all being IC [ 72 ]. There were four cases of C. albicans and one each of C. glabrata , C. dubliniensis , and C. krusei .…”
Section: Ifi In Sot: India Vs the Worldmentioning
confidence: 99%